Observer-based linear parameter varying H∞ tracking control for hypersonic vehicles. (10th November 2016) - Huang, Yiqing; Shao, Shouchen; Peng, Kai; Jiang, Ming
This article aims to develop observer-based linear parameter varying output feedback H ∞ tracking controller for hypersonic vehicles. Due to the complexity of an original nonlinear model of the hypersonic vehicle dynamics, a slow–fast loop linear parameter varying polytopic model is introduced for system stability analysis and controller design. Then, a state observer is developed by linear parameter varying technique in order to estimate the unmeasured atti tude angular for slow loop system. Also, based on the designed linear parameter varying state observer, a kind of attitude tracking controller is presented to reduce tracking errors for all bounded reference attitude angular inputs. The closed-loop linear parameter varying system is proved to be quadratically stable by Lypapunov function technique. Finally, simulation results show that the developed linear parameter varying H ∞ controller has good tracking capability for reference commands.